Q: 4x2 plus 2xy-3y2 plus -2x2 plus 5xy-2y2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

12

Reading this as: 4x2-6=2x2 This implies that: -6=-2x2 3=x2 x=sqrt(3) and x=-sqrt(3) So x can equal plus or minus the square root of 3

4x2+2x-20 2x2+x-10 2x2+5x-4x-10 x(2x+5)-2(2x+5) (x-2)(2x+5)

-4x2 + 6x + 40 = 0 ∴ -2x2 + 3x + 20 = 0 ∴ -2x2 - 8x + 5x + 20 = 0 ∴ -2x(x + 4) + 5(x + 4) = 0 ∴ (5 - 2x)(x + 4) = 0 ∴ x ∈ {5/2, -4}

4x2 - 6x - 12 = 2 (2x2 - 3x - 6) There are no integer roots, the approximate roots are 2.64 and -1.14

Related questions

4x2-x+2x2 is 6x2-x when simplified

12

Reading this as: 4x2-6=2x2 This implies that: -6=-2x2 3=x2 x=sqrt(3) and x=-sqrt(3) So x can equal plus or minus the square root of 3

4x2+2x-20 2x2+x-10 2x2+5x-4x-10 x(2x+5)-2(2x+5) (x-2)(2x+5)

124 (?) Try to do it on the calculator on your computer * * * * * No, 4x2 + 14x + 12 is factorised, as follows: 4x2 + 14x + 12 = 2(2x2 + 7x + 6) = 2(x + 2)(2x + 3).

(2x2 - 1)(2x2 - 1) or (2x2 - 1)2

First you should combine equal terms. For example, 2x2 and -4x2 can be combined as -2x2. Then you can use the quadratic formula.Additonal Answer:-2x2+5x+3-4x2+22 = 0Collect like terms: -2x2+5x+25 = 0Divide al terms by -1: 2x2-5x-25 = 0Factorise: (2x+5)(x-5) = 0Solutions are: x = -5/2 or x = 5

-4x2 + 6x + 40 = 0 ∴ -2x2 + 3x + 20 = 0 ∴ -2x2 - 8x + 5x + 20 = 0 ∴ -2x(x + 4) + 5(x + 4) = 0 ∴ (5 - 2x)(x + 4) = 0 ∴ x ∈ {5/2, -4}

2x2(2x - 1)(2x + 1)(4x2 + 1)

4x2 + 14x + 12 = 2(2x2 + 7x + 6) = 2(2x + 3)(x + 2)

Because you are just adding the same variable to itself, the variable does not change. in the same way that 2 + 2 is 4, 2x2 + 2x2 is 4x2.

72 ^ 9x8 ^ ^ 3x3 4x2 ^ 2x2